ARTS AND MACHINE CIVILIZATION INTERNATIONAL SCIENTIFIC CONFERENCE / МЕЖДУНАРОДНАЯ НАУЧНАЯ КОНФЕРЕНЦИЯ «ИСКУССТВО И МАШИННАЯ ЦИВИЛИЗАЦИЯ» - DUKOV YEVGENY V. / ДУКОВ Е.В.; EVALLYO VIOLETTA D. / ЭВАЛЛЬЕ В.Д. (Наука телевидения, 2021)
The text reviews the Arts and Machine Civilization International Scientific Conference. The conference took place on March 30—April 2, 2021, and was organized by the State Institute for Art Studies, GITR Film and Television School, and the Saint Petersburg State University. SIAS has been hosting conferences on contemporary culture, screen art and television for 17 years. This year, for the first time in the history of such forums, the researchers were tasked with analyzing the new things that machines have brought to the arts and, in general, to human life. The conference took its special place among the forums held over the past year in Russia and abroad in the following areas: artificial intelligence (Artificial Intelligence Journey, Moscow,Russia); machine learning (International Conferenceon Machine Learning, Vienna, Austria; 3rd International Conference on Machine Learning and Machine Intelligence, Hangzhou, China); civilization of knowledge (Civilization of Knowledge: Russian Realities, Moscow, Russia), etc. The novelty of the conference lies in the unification of the seemingly incompatible phenomena: art and machine civilization. As is commonly known, art was traditionally opposed to technology as something alien, sometimes hostile, although the both were born in human mind and created by human hands. Until now, the expression “machine civilization” in art has been used mainly in the genre of fantasy and with an emphasis on its negative connotations. The purpose of the conference was to comprehend the artistic practices in the era of machine civilization, get acquainted with current hypotheses, publish new facts and discuss modern terminologies (law of spontaneity, law of semantic uncertainty, algorithmic apophenia, post-opera, artificial life and new vitality). Along with the study of new challenges, old issues were raised, which became in demand in the machine civilization: originals and copies of artworks, the boundaries of conventionality and overcoming distrust in new media, narratives and poetics in serious and entertaining screen genres. The conference reports were divided into six blocks: Theoretical Models, Screen Arts—Cinema, Fine Arts, Music, PC Games, and Digitalization.